Retinal micro-vascular and aortic macro-vascular changes in postmenopausal women with primary hyperparathyroidism. Issue 1 (December 2018) - Pepe, Jessica; Cipriani, Cristiana; Tedeschi, Massimiliano; Curione, Mario; Parravano, Mariacristina; Varano, Monica; Biamonte, Federica; Colangelo, Luciano; Minisola, Salvatore
Abstract Aim of the study was to evaluate the micro and macro-vascular changes in patients with primary hyperparathyroidism (PHPT) compared to controls. 30 postmenopausal PHPT women (15 hypertensive and 15 normotensive) and 30 normotensive controls underwent biochemical evaluation of mineral metabolism and measurements of arterial stiffness by 24 hour ambulatory blood pressure monitoring. Retinal microcirculation was imaged by a Retinal Vessel Analyzer. PHPT patients also underwent bone mineral density measurements and kidney ultrasound. PHPT patients had higher mean calcium and parathyroid hormone values compared to controls. Evaluating macro-vascular compartment, we found higher values of 24 hours-systolic, diastolic blood pressure, aortic pulse wave velocity (aPWV) and aortic augmentation index (Aix) in hypertensive PHPT, but not in normotensive PHPT compared to controls. The eye examination showed narrowing arterial and venular diameters of retinal vessels in both hypertensive and normotensive PHPT compared to controls. In hypertensive PHPT, 24 hours systolic blood pressure was associated only with parathyroid hormone (PTH) levels (beta = 0.36, p = 0.04). aPWV was associated with retinal diameter (beta = −0.69, p = 0.003), but not with PTH. Retinal artery diameter was associated with PTH (beta = −0.6, p = 0.008). In the normotensive PHPT, only PTH was associated with retinal artery diameter (beta = −0.60, p = 0.01) and aortic AIx (beta = 0.65, p = 0.02). In conclusion, we found macro-vascular impairment in PHPT and that micro-vascular impairment is negatively associated with PTH, regardless of hypertension in PHPT.